Citronellol inhibits the activity of AtSRT1 to increase IAA content and signal transduction, promoting the growth of A. thaliana - Jin-Rui Wen; Hong-Yan Nie; Hong-Xin Liao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Chemical and Biological Technologies in Agriculture)
Abstract Histone acetylation is a key epigenetic modification involved in plant development. Although histone deacetylase inhibitors (HDACi) are commonly studied in human diseases, their role in regulating histone deacetylation in plants remains unclear. This study explores the function of Citronellol, a volatile small molecule, as a plant-derived HDACi using Arabidopsis thaliana (L.) Heynh (A. thaliana) as a model. Citronellol at concentrations of 3 and 6 mM enhanced both root development and aboveground growth. Enzyme activity assays, molecular docking, and molecular dynamics simulations showed that Citronellol binds to specific residues (PHE:64, ARG:65, MET:1, and ILE:214) of the histone deacetylase AtSRT1 in Arabidopsis, inhibiting its activity and elevating H3K9ac levels. Integrated RNA-seq and ChIP-seq analyses revealed that Citronellol increased the expression of genes linked to growth and development, including ATCTH, CPL3, IBR5, TCP4, and KUA1, through enhanced histone acetylation and activation of plant hormone signaling pathways. These findings provide new insights into the epigenetic regulation of plant growth by Citronellol, identifying it as a novel HDACi. Citronellol could serve as an effective plant growth regulator, offering valuable applications for agricultural development.  Graphical Abstract